Total Synthesis of Terpioside B. Issue 45 (13th July 2020) - Inaba, Kazuki; Endo, Masato; Iibuchi, Naoto; Takahashi, Daisuke; Toshima, Kazunobu
Abstract: The first total synthesis of terpioside B (1 ) has been accomplished. Key steps include the stereoselective installments of a set of challenging 1, 2‐ cis ‐glycosidic linkages. Thus, α(1, 4)‐linked d ‐galactoside was effectively constructed from a 1, 2‐anhydrogalactose donor and an unprotected 1, 6‐anhydrogalactose acceptor by using a boron‐mediated aglycon delivery (BMAD) method. In addition, α‐l ‐fucofuranosides were stereoselectively and simultaneously constructed by remote group‐assisted 1, 2‐ cis ‐α‐stereoselective glycosylations. Abstract : Glycosphingilipids : Total synthesis of a natural glycosphingolipid possessing an l ‐fucofuranoside residue is described (see figure). The synthetic strategy involves three types of glycosylations: i) boronic acid‐catalyzed regio‐ and 1, 2‐ cis ‐α‐stereoselective glycosylation, ii) remote group‐assisted 1, 2‐ cis ‐α‐stereoselective glycosylation, and iii) neighboring‐group‐assisted 1, 2‐ trans ‐β‐stereoselective glycosylation.